2016
DOI: 10.4103/1319-3767.187604
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related blood stream infection in patients receiving long-term home parenteral nutrition: Tertiary care hospital experience in Saudi Arabia

Abstract: Background/Aim:Parenteral nutrition (PN) is a lifesaving therapy for patients with many severe conditions, including intestinal failure. Some patients require long-term PN therapy, which makes home parenteral nutrition (HPN) an attractive option to improve the quality of life. Among the most common and serious complications observed in these patients are catheter-related blood stream infections (CRBSIs). The aim of our study is to determine the frequency of CRBSI among patients receiving long-term HPN.Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Staphylococcus aureus is the major pathogen causing CVC infections (39%), followed by CONS (16%) and K. pneumoniae (10%). These results agree with those of previous studies 39,40 . Most studies demonstrated that Gram-negative bacteria are the major cause of catheter-related blood stream infection, but these studies used blood samples to detect infection.…”
Section: Discussionsupporting
confidence: 94%
“…Staphylococcus aureus is the major pathogen causing CVC infections (39%), followed by CONS (16%) and K. pneumoniae (10%). These results agree with those of previous studies 39,40 . Most studies demonstrated that Gram-negative bacteria are the major cause of catheter-related blood stream infection, but these studies used blood samples to detect infection.…”
Section: Discussionsupporting
confidence: 94%
“…12 HPN programmes are considered new in Saudi Arabia, and the first programme in the region was established in 2004 in a governmental tertiary care hospital. 18 Our study confirmed that HPN is underutilized. Thus, the underutilization of HPN services needs to be addressed by the country’s healthcare workforce.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, chronic diseases can overlap as diabetic patients are at high risk of having renal dysfunction and require hemodialysis; almost 40% of dialysis individuals are diabetic [ 21 ]. A recent study on tertiary care hospitals in Saudi Arabia observed that infections associated with bloodstream catheters occurred at a rate of 2.9 per 1000 days, and Staphylococcus species were the most common causative organisms [ 22 ]. Cardiovascular patients are also at high risk of infections because of invasive procedures used, including transplantation, congenital heart disease, and coronary artery bypass grafts.…”
Section: Introductionmentioning
confidence: 99%